2010
DOI: 10.1373/clinchem.2009.133363
|View full text |Cite
|
Sign up to set email alerts
|

Peptides Generated Ex Vivo from Serum Proteins by Tumor-Specific Exopeptidases Are Not Useful Biomarkers in Ovarian Cancer

Abstract: Background: The serum peptidome may be a valuable source of diagnostic cancer biomarkers. Previous mass spectrometry (MS) studies have suggested that groups of related peptides discriminatory for different cancer types are generated ex vivo from abundant serum proteins by tumor-specific exopeptidases. We tested 2 complementary serum profiling strategies to see if similar peptides could be found that discriminate ovarian cancer from benign cases and healthy controls. Methods: We subjected identic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…On the contrary, Timms et al . recently reported that MALDI MS peptide profiling was unable to accurately diagnose OvCa from healthy controls, though the endogenous peptides could provide some diagnostic insight [13]. Needless to say, greater characterization of the endogenous peptidome of various biospecimens related to OvCa is needed to truly assess whether or not peptide-based biomarkers are clinically useful.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, Timms et al . recently reported that MALDI MS peptide profiling was unable to accurately diagnose OvCa from healthy controls, though the endogenous peptides could provide some diagnostic insight [13]. Needless to say, greater characterization of the endogenous peptidome of various biospecimens related to OvCa is needed to truly assess whether or not peptide-based biomarkers are clinically useful.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper, Ziptips and magnetic beads were also compared for human serum peptide profiling, and it was determined that Ziptips were a better desalting method in spectral quality, reproducibility, and time consumption. 43 …”
Section: Resultsmentioning
confidence: 99%
“…Proteomic data sets comprise: ovarian cancer data from the UKOPS trial [6]; ovarian cancer (OC ), breast cancer (BC ) and heart disease (HD ) samples collected in the UKCTOCS trial 1 ; Competition data provided by the Leiden Clinical Mass Spectrometry Proteomic Diagnosis Competition and preprocessed as described in [7]; Ciphergen's 7 biomarkers of UKOPS data [8]. The other medical data sets are shortened Abdominal pain data [9], which comprises 33 symptoms of acute abdominal pain, and Microarray data of lung cancer, colon cancer and breast cancer patients provided in the ICMLA 2009 Challenge [10].…”
Section: Datamentioning
confidence: 99%